Standard form ax 2 + bx + c a, b, c are real numbers
1. Write expression in standard form 2. Make a table to find factors of ac whose sum is b Factors ac Sum b 3.List all factors of ac, then add the factors and write the sum in 2 nd column. 4.Keep listing factors of ac until you get a sum of b 5.Circles the factors whose sum was b 6.Write out ax 2 + (factor)x + (factor)x + c 7.Use grouping method to finish factoring 8.Check your answer.
To solve by factoring the quadratic must be set equal to zero. You’ll use the Zero Product Property to solve. Zero Product Property states ◦ Ab = 0, then a = 0 or b = 0. ◦ Our question will look something like: ◦ (x + 3)(x – 7) = 0 ◦ So (x + 3) = 0 OR (x – 7) = 0, then we’ll have to solve for two different x answers.